Some significative characteristics of lexical units indicating children in Russian and Chinese - Wenjuan, Wang (Journal of the Belarusian State University. Philology, 2019)
The article investigates the lexical units denoting children in modern Russian and Chinese. An attempt was made to determine age limits of childhood by referring to texts which include lexemes with such meanings as ‘baby’, ‘child’, ‘teenager’ in the Russian National Corpus and Corpus of Chinese in the Communication University of China. The study shows that a fragment of the language worldview, which can be defined as childhood in its main characteristics is the same for the Russian and the Chinese languages. The differences are often due to the language structure rather than due to the differences in the structure of peoples’ worldviews.
Keywords: age; childhood; significative characteristics; lexical units indicating children; baby; child; teenager; Russian language; Chinese language